2016
DOI: 10.1111/joca.12137
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Saving and Food Security: Evidence from an Asset‐Building Program for Families in Poverty

Abstract: This study examines food insecurity among children of participants in a federally funded savings program in the United States, the Individual Development Account (IDA) program. We measure child food insecurity of savings program families by using the eight questions of the Current Population Survey's Food Security Supplement. About 39.4% of savings program families report food insecurity. No differences in children's food hardship between current and past program participants were identified. Examining predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…It also provides financial education and training on budgeting and credit repair and other asset-specific training. The research presented in this review found no significant difference in children’s food insecurity between those newly enrolled on the programme and those who had graduated from the programme [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…It also provides financial education and training on budgeting and credit repair and other asset-specific training. The research presented in this review found no significant difference in children’s food insecurity between those newly enrolled on the programme and those who had graduated from the programme [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dunn and Mirzaie ( 2016 ) found that, while bank loans and mortgages declined during the Great Recession, other types of consumer debt, including payday loans (38%), credit card (18%), and student loan debt (23%), increased from 2008 to 2011. The use of risky credit products like payday loans have been linked to higher food insecurity for children in low‐income families, whereas thriftiness and saving behaviors lead to lower food insecurity (Loibl et al, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The largest source of informal lending is family and friends (Lee and Persson 2016). Access to loans from these sources has been shown to be a significant economic factor in mitigating shocks related to unexpected expenses (Loibl et al 2017), especially for low-income families (Loke 2016) and those who are self-employed (Davutyan and Öztürkkal 2016). Family loans, however, depend on the breadth of social networks and the wealth of social network members (Fan et al 2017).…”
Section: Loans From Familymentioning
confidence: 99%